2007
DOI: 10.1128/cvi.00079-07
|View full text |Cite
|
Sign up to set email alerts
|

Aggregating Phenotype in Lactobacillus crispatus Determines Intestinal Colonization and TLR2 and TLR4 Modulation in Murine Colonic Mucosa

Abstract: The colonic microbiota is a major modulator of the mucosal immune system; therefore, its manipulation through supplementation with probiotics may significantly affect the host's immune responses. Since different probiotics seem to exert various effects in vivo, we tested the relevance of the autoaggregation phenotype on the intestinal persistence of lactobacilli and their ability to modulate the host's innate immune responses. After 14 days of diet supplementation, the aggregating strain Lactobacillus crispatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 59 publications
(76 reference statements)
7
46
1
11
Order By: Relevance
“…Furthermore the aggregating strain Lactobacillus crispatus M 247 was recovered from the faeces and colonic mucosa of mice after 14 days of diet supplementation but an In vitro properties of two probiotic Lactobacillus aggregation-deficient isogenic mutant MU5 was absent, leading to the conclusion that the aggregation phenotype in Lb. crispatus determines intestinal colonization in murine colonic mucosa (Voltan et al, 2007). These in vivo studies indicate that bacteria with aggregating phenotypes persist longer in the gastrointestinal tract compared with nonaggregating phenotype and that adhesion and aggregation appear to be correlated.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Furthermore the aggregating strain Lactobacillus crispatus M 247 was recovered from the faeces and colonic mucosa of mice after 14 days of diet supplementation but an In vitro properties of two probiotic Lactobacillus aggregation-deficient isogenic mutant MU5 was absent, leading to the conclusion that the aggregation phenotype in Lb. crispatus determines intestinal colonization in murine colonic mucosa (Voltan et al, 2007). These in vivo studies indicate that bacteria with aggregating phenotypes persist longer in the gastrointestinal tract compared with nonaggregating phenotype and that adhesion and aggregation appear to be correlated.…”
Section: Discussionmentioning
confidence: 70%
“…farciminis 3699 involves carbohydrate-lectin interactions and/or proteinaceous components present on the surface. Autoaggregation is a known property of some Lactobacillus isolates (Collado et al, 2007(Collado et al, , 2008 and allows the formation of biofilm in the gastrointestinal tract which contributes, as a physico-chemical barrier, to the preservation of the intestinal wall, along with the stimulation of the immune system (Jankovic et al, 2003;Castagliuolo et al, 2005;Voltan et al, 2007;Turpin et al, 2010), and to protection against colonization by pathogenic bacteria (Collado et al, 2007(Collado et al, , 2008. Furthermore, bacteria with a high autoaggregation potential will more easily colonize the intestinal and urogenital tracts (Boris et al, 1998;Cesena et al, 2001;Collado et al, 2005Collado et al, , 2007Collado et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, based on cell surface hydrophobicity, only 9 isolates (LBF 01, LBF 05, LBF 08, LBF 11, LBF 13 A, LBF 20, LBF89, LBF90, LBF91) were selected for further characterization.Cell adhesion, a multistep process, involves contact of the bacterial cell membrane and intermingling surfaces while aggregation may take place between cells of the same strain (auto-aggregation) or between different species and strains (co-aggregation). Aggregation has been considered as an important mechanism for genetic exchange, adhesion, and colonization in the host environments, as well as Immuno modulation of colonic mucosa (Cesena et al, 2001, Voltan et al, 2007. Savedboworn et al, (2014) concluded that most of the LAB exhibited a strong autoaggregation after 5 h of incubation like KMUTNB 5-8 strain showed highest autoaggregation ability of 96.09%.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Zahvaljujući sposobnosti agregacije, soj Lb. crispatus M247 bolje preživljava u debelom crevu od svog mutanta MU5 koji je izgubio tu sposobnost (Voltan et al, 2007). Takođe, Lb.…”
Section: Sposobnost Agregacije Kod Laktobacilaunclassified